Single Nucleotide Mutagenesis of the TaCHLI Gene Suppressed Chlorophyll and Fatty Acid Biosynthesis in Common Wheat Seedlings - Wang, Chaojie; Zhang, Lili; Li, Yingzhuang; Ali Buttar, Zeeshan; Wang, Na; Xie, Yanzhou; Wang, Chengshe (Frontiers in Plant Science, 2020)
Wheat (Triticum aestivum L.) is one of the most important crops in the world. Chlorophyll plays a vital role in plant development and crop improvement and further determines the crop productivity to a certain extent. The biosynthesis of chlorophyll remains a complex metabolic process, and fundamental biochemical discoveries have resulted from studies of plant mutants with altered leaf color. In this study, we identified a chlorophyll-deficiency mutant, referred to as chli, from the wheat cultivar Shaannong33 that exhibited an obvious pale-green leaf phenotype at the seedling stage, with significantly decreased accumulation of chlorophyll and its precursors, protoporphyrin IX and Mg-protoporphyrin IX. Interestingly, a higher protoporphyrin IX to Mg-protoporphyrin IX ratio was observed in chli. Lipid biosynthesis in chli leaves and seeds was also affected, with the mutant displaying significantly reduced total lipid content relative to Shaanong33. Genetic analysis indicated that the pale-green leaf phenotype was controlled by a single pair of recessive nuclear genes. Furthermore, sequence alignment revealed a single-nucleotide mutation (G664A) in the gene TraesCS7A01G480700.1, which encodes subunit I of the Mg-chelatase in plants. This single-nucleotide mutation resulted in an amino acid substitution (D221N) in the highly conserved domain of subunit I. As a result, mutant protein Tachli-7A lost the ability to interact with the normal protein TaCHLI-7A, as assessed by yeast two-hybrid assay. Meanwhile, Tachli-7A could not recover the chlorophyll deficiency phenotype of the Arabidopsis thaliana SALK_050029 mutant. Furthermore, we found that in Shaannong33, the protoporphyrin IX to Mg-protoporphyrin IX ratio was growth state-dependent and insensitive to environmental change. Overall, the mutation in Tachli-7A impaired the function of Mg-chelatase and blocked the conversion of protoporphyrin IX to Mg- protoporphyrin IX. Based on our results, the chli mutant represents a potentially useful resource for better understanding chlorophyll and lipid biosynthetic pathways in common wheat.